PENDAMPINGAN MANAGEMEN KONTEN DAN KARYA ILMIAH REMAJA DI SMP NEGERI 2 ABIANSEMAL BADUNG - Ni Luh Putu Tejawati; I Gusti Ayu Rai; I Made Subrata; I Made Surat; I Made Darmada (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This community service activity aims to provide training and assistance in writing scientific papers for teenagers and managing scientific literacy content at SMP Negeri 2 Abiansemal, Badung. The main problems faced are the less than optimal implementation of the Youth Scientific Paper (KIR) extracurricular activities, minimal assistance, and lack of student motivation in writing scientific papers. The method of implementing this activity uses a participatory approach through the stages of socialization, training, direct assistance, and evaluation and follow-up. The results of the activity show that of the six KIR groups formed, only one group actively communicates and continues online writing consultations. This shows that student enthusiasm still needs to be fostered sustainably with support from supervising teachers and motivation strengthening strategies. However, this activity succeeded in increasing students' knowledge in understanding the structure of scientific papers and scientific presentation techniques. This activity also builds awareness of the importance of scientific literacy from an early age as part of improving the quality of human resources. It is hoped that further assistance can continue to be carried out in order to reactivate KIR activities in schools consistently and sustainably.